HOMOSEXUALITY IN ANDREW SEAN GREER’S LESS NOVEL (Universitas Pamulang, 2021)
The aim of the study is to analyze the issue of homosexuality which is shown by the main character in Andrew Sean Greer’s Less novel (2017). This study uses Queer Theory by Annamarie Jagose in her book entitled Queer Theory: An Introduction (1996) regarding homosexuality. Meanwhile, this study applies a qualitative and textual approach that presents an analysis in the form of essay. The results of this study found out the causes of homosexual, exploring the social life and past life. Therefore, it impacts the main character’s sexual orientation as a homosexual and the way he struggles against social judgments. The impact of the struggles, Arthur Less undertakes self-acceptance process regarding his gay identity, dealing with discrimination, and becoming a gay writer.